Challenges and Constraints in Conducting the Field Residential Posting (FRP) during COVID-19 Pandemic: a Case Study - Osman Ali (Asian Journal of Medicine & Health Sciences, 2021)
The field residential posting (FRP) is experiential learning that enables medical students in the RCMP to develop skills in community diagnosis and to plan intervention programs to address health issues in the community. Due to the COVID-19 pandemic, students posted in the community must abide to strict standard operating procedures (SOPs) set by the government. At the community diagnostic stage, the key informant interview and focus group discussion took place both at the community meeting location and by telephone. The sample survey was largely conducted using a web-based application (Google form). The intervention program was planned according to the ranking of problems using the nominal group technique. To avoid crowds, the intervention was divided into several activities that use different times and locations. With the limitation and constraints, the FRP is still able to impart some good knowledge and experience to the students. The program applied different types of learning required for developing attributes for future physicians such as experience, collaboration, participation, technology, involvement, and community. The COVID-19 pandemic enabled medical students to gain knowledge and information and participate in community events. However, given the constraints they encountered during the FRP, they will be stronger to face the reality of the future.